A 15-year retrospective study of 160 cases of benign lip lesions. Issue 12 (11th December 2015) - Arslan, S; Çobanoğlu, B; Ural, A; Sayğin, İ; Işik, A Ü
Abstract: Objective: This study aimed to describe the results of a retrospective analysis of a specific cohort of patients with benign lip lesions encountered in the last 15 years in the School of Medicine at Karadeniz Technical University. Method: A total of 312 patients were managed for lip lesions during the period 2000–2014. Data from 160 samples of benign lip biopsies were retrieved from the pathology laboratory records. Results: The study group included 20 different histopathological types of lesions, with mucocele being the most frequent lesion (43.13 per cent). The other frequent lesions were chronic inflammatory infiltrate (11.25 per cent), intradermal naevus (5.63 per cent), pyogenic granuloma (5.63 per cent), fibroma (5 per cent) and papilloma (5 per cent). Mucocele was significantly more common in younger patients ( p < 0.001). Conclusion: Knowledge of the epidemiology and distribution of oral mucosal lesions is essential to promote early diagnosis and treatment. Further epidemiological studies exploring the causal relationships and risk factors for lip lesions are necessary for a better understanding of lip diseases.